Idiomatic Expression Found in Movie Script of The Beauty and The Beast : A Semantics Study - Ilmi Fadillah; Puspita Sari (Ethical Lingua: Journal of Language Teaching and Literature, 2022)
The purpose of this study is to identify the types of idiomatic expressions in the script of the movie "Beauty and the Beast" and to identify the patterns of idiomatic expressions. The theory for analyzing types and patterns comes from O'Dell & McCarthy (2017) and Joodi (2012). This research uses a descriptive qualitative method. In collecting data, this research used the forms of classification, documentation, and monolingual dictionaries. After analyzing the data, it is found that there are 30 data divided into 20 data of fixed statements (66,67%), 5 data of slang (16,67%), 3 data of proverbs (10%), and 2 data of clichés (6,66%). It can be identified some idiomatic expression patterns used in The Beauty and The Beast movie script such as noun phrases, transitive verb phrases, verbal phrases, prepositional phrases, word pairs, and pattern sentences. The type of idiomatic expression that is the most dominant and often appears in the script of The Beauty and The Beast is fixed statements.